Effects of Braille Mathematical Code Instruction and Concrete Materials on Mathematics Performance in Primary School Learners with Total Blindness: A Quasi-Experimental Study in Oyo State, Nigeria - Hammed Temitope Rasheed; Eniola Michael Sunday (Utan Kayu Publishing, 2026)
Mathematics learning for learners with total blindness is constrained by limited access to symbolic and tactile representations. This study examined whether Braille Mathematical Code (BMC) instruction and Concrete Materials (CM) improve mathematics performance among primary-school learners with total blindness in Oyo State, Nigeria, and assessed gender and academic self-efficacy effects. Using a pretest–posttest control-group quasi-experimental design with three treatment conditions (BMC, CM, and conventional instruction), 45 learners with total blindness completed a six-week program (1-week pretest, 4-week intervention, 1-week posttest). Screening and measurement used a Teacher Observation Report, Snellen Chart, an Academic Self-Efficacy Scale, and a Braille-accessible Mathematics Performance Assessment. Posttest performance was analyzed with ANCOVA controlling for pretest scores, followed by Bonferroni-adjusted pairwise comparisons; gender differences were examined with an independent-samples t test, and self-efficacy categories with one-way ANOVA. ANCOVA showed a significant main effect of treatment on posttest performance, F(1,35)=12.46, p=.001, ηp²=.263, although Bonferroni pairwise contrasts were non-significant. Gender was not significant (t(43)=0.709, p=.484). Academic self-efficacy differed significantly across categories, F(2,42)=7.89, p=.001. Accessible instructional supports are associated with improved mathematics outcomes for learners with total blindness, and self-efficacy is a relevant learner factor. Future work should strengthen cluster-aware designs and fidelity reporting in schools.